The Effects of a Bioenergy Economy Based Program on Attention Bias Modification in People With High Anxiety Sensitivity - Keyvanipour, Maryam; Goli, Farzad; Bigdeli, Amanullah; Boroumand, Amirreza; Rafienia, Parvin; Sabahi, Parviz (International Clinical Neuroscience Journal, 2019)
Background: According to scientific evidence, high levels of sensitivity anxiety are one of the predictors of panic attacks, anxiety, and depression. The multidimensional anxiety sensitivity (cognitive, social, and physiological) is base on cognitive biases such as attention biases which are due to selecting threatening stimuli instead of neutral or positive stimuli. Despite the initial promise, attention bias modification (ABM) has a limited effect on reducing anxiety. This study aims to modify attention bias by reducing the focus on the threatening stimuli based on Bioenergy Economy (BEE) protocol; as an integrated model of care. Methods: The present study is base on a quasi-experimental design with pre-test and post-test and follow-up in both groups. Thirty women between the ages of 23 to 50 selected from the patients referred to Bozorgmehr Neurology clinic in Mashhad. People who scored more than 70 in anxiety test, were randomly put into the experimental and control groups. The data collection tool was dot-probe test. The experimental group participated in the entire BEE protocol. Results: The mean score sensitivity anxiety of the experimental group in the pre-test, post-test, and follow-up was significantly lower than those in the control group by using multivariate analysis of covariance. Also, the mean score of the experimental group in dot-probe test, neutral reaction time, emotional response time, and interference score in the post-test phase, as well as the components of dull reaction time and sensitive response time in the follow-up and post-test were significantly lower than the control group. Conclusion: The BEE protocol is effective in ABM and reducing high sensitivity anxiety.